The Convergence Technique: A Method for the Planning and Programming of Research Efforts - Carrese, Louis M.; Baker, Carl G. (Management Science, 1967)
The difficulties encountered in attempts to apply directly some of the standard network analysis techniques to the planning of research programs are discussed. The particularized requirements for a planning system suitable for research efforts are identified, and a technique developed specifically for the planning and programming of research efforts is described. Basically, the technique involves the formulation of a series of flows and arrays depicting major program elements and individual projects, sequentially ordered on the basis of research logic, and graphically represented by a matrix which relates research performance to resources required (including personnel, materials, equipment and facilities, and funds). Because of the nature of research, the technique was developed to avoid the formulation of tight networks with sharp time-to-completion estimates for each project. The application of this technique to two biomedical research programs of the National Cancer Institute is discussed.